2020
DOI: 10.1016/j.childyouth.2020.105508
|View full text |Cite
|
Sign up to set email alerts
|

Child welfare workers and peritraumatic distress: The impact of COVID-19

Abstract: Highlights This exploratory study examined COVID-19 related peritraumatic distress among child welfare workers (N=1,996) in one southeastern state in the United States (U.S.). Nearly half of all participants were experiencing mild or severe distress. Those identifying as married, heterosexual/straight, a supervisor, more financially stable, and in better physical and mental health (respectively) were experiencing less distress than others in the sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 28 publications
2
46
0
3
Order By: Relevance
“…In line with our study, in the range of moderate to high and severe levels of burnout are reported about 60% of social workers [30,32], even before the pandemic outbreak. A study that examined COVID-19 related peritraumatic distress (the physiological and/or emotional distress experienced by an individual during a traumatic event) among child welfare workers (N=1996) in US indicating that nearly half of all participants (46.4%) scored in a range indicating mild or severe peritraumatic distress that may lead to professional burnout as the authors state [4]. The only study on burnout during the pandemic in Romania identified show higher levels of work related and personal burnout among employees in the human resources department (M=2.23, SD=0.81), compared to those in a technical department (M=1.76, SD=0.62) in a multinational company [45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with our study, in the range of moderate to high and severe levels of burnout are reported about 60% of social workers [30,32], even before the pandemic outbreak. A study that examined COVID-19 related peritraumatic distress (the physiological and/or emotional distress experienced by an individual during a traumatic event) among child welfare workers (N=1996) in US indicating that nearly half of all participants (46.4%) scored in a range indicating mild or severe peritraumatic distress that may lead to professional burnout as the authors state [4]. The only study on burnout during the pandemic in Romania identified show higher levels of work related and personal burnout among employees in the human resources department (M=2.23, SD=0.81), compared to those in a technical department (M=1.76, SD=0.62) in a multinational company [45].…”
Section: Discussionmentioning
confidence: 99%
“…High job demands and low resources are known to be the primary reasons for burnout [51]. Stress factors related to clients refer primarily to the lack of direct contact, the risk of being a carrier (asymptomatic) and contamination in two ways -both by the social worker and by the beneficiary [4,7], difficulties related to technology (absence of it or digital skills) and sometimes managing fears, panic of beneficiaries. It is important to mention the factor "the desire to help more than I could do", present in almost half of the social workers included in the study, an indicator of the social worker's mission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the unique and increased challenges faced by child welfare professionals during COVID-19 is emerging. Miller et al, (2020b) found that child welfare workers in the US reported above-normal levels of stress. Jentsch and Schnock (2020) found that child welfare workers in Germany also experienced heightened stress during COVID-19, which the authors suggested may be due in part to workers’ concerns about effectively identifying potential cases of child maltreatment absent the support normally provided by teachers and others, as well as the difficulty of maintaining contact with clients while abiding by physical distancing rules.…”
Section: Introductionmentioning
confidence: 99%